2018
DOI: 10.3389/fvets.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Signal Alterations in Paraspinal Muscles in Dogs with Acute Thoracolumbar Intervertebral Disk Extrusion

Abstract: Muscle signal alteration detected on MRI is seen in diverse pathologic conditions. We observed signal alterations within the paraspinal muscles in dogs with acute thoracolumbar intervertebral disk extrusion. The aim of this retrospective study was to describe MRI features of paraspinal muscle signal alteration in dogs with acute thoracolumbar intervertebral disk extrusion and to investigate an association of the signal alterations with neurological grade, type and location of intervertebral disk extrusion, deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 17 publications
3
26
1
Order By: Relevance
“…Our study reports the prevalence and signal characteristics of muscle changes on MRI in dogs with surgically confirmed IVDE. A recently published study (Trampus et al 2018) reported that paravertebral muscle changes occur in 36% of dogs with IVDE, which contrasts with the number we report (6.9%). Possible reasons for this discrepancy are the larger size of our study population and the lack of STIR images in some cases in the other study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study reports the prevalence and signal characteristics of muscle changes on MRI in dogs with surgically confirmed IVDE. A recently published study (Trampus et al 2018) reported that paravertebral muscle changes occur in 36% of dogs with IVDE, which contrasts with the number we report (6.9%). Possible reasons for this discrepancy are the larger size of our study population and the lack of STIR images in some cases in the other study.…”
Section: Discussioncontrasting
confidence: 99%
“…Non-ambulatory paraparesis was the most common presentation in the MSIC group, whereas the comparator group predominantly remained ambulatory. This difference is in agreement with a previous report (Trampus et al 2018).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the latter group of dogs, the muscle groups that were affected were in close proximity to the nerve root and meningeal changes, leading to speculation that meningeal disease might extend into adjacent nerve roots and muscles . Alternatively, the observed changes could be secondary to denervation . Denervation can cause diffuse edema throughout an affected muscle, because of shifting of water from intracellular to extracellular spaces .…”
Section: Discussionmentioning
confidence: 99%